A Conceptual Analysis of Metaphors Engendering HIV and AIDS-Related Stigma and Discrimination in Kisii County, Kenya - Maroko, Geoffrey Mokua; Mokua, Gladys Nyamoita; Nyakundi, Augustus Onchari; Onyambu, Meshack Ondora (Language Circle: Journal of Language and Literature, 2020)
Metaphors are mapped across two conceptual domains where A is B. Metaphorical expressionsare defined by dimensions including novelty, conventionality, abstractness and concreteness. The AbaGusii of Western Kenya is a highly conservative community of Bantu speakers of Western part of Kenya. They view HIV and Aids as taboo that cannot be the subject of discussion in public. Hence, People Living with HIV (hereafter PLHIV) are stigmatized and discriminated. The purpose of this paper is to analyse the metaphorical words and concepts that engender HIV and Aids-related stigma and discrimination in Kisii County. Descriptive narratives were elicited from HIV support providers using focus group discussions and follow-up interviews. The narratives were analysed in terms of five attributes of stigma and discrimination within the conceptual metaphor theory. Results revealed some culturally ingrained metaphors that evoke stigma and discrimination. The paper advocates for language management efforts using success stories in HIV and Aids management to construct positive messages to counter the negative metaphors.